Penerapan Pembelajaran Berdiferensiasi (Gaya Belajar) untuk Meningkatkan Hasil Belajar Muatan IPAS Materi Sistem Pernapasan Manusia Kelas V SDN Sukowati Kapas Bojonegoro - Ryandini Dwi Puspita; Hendrik Pandu Paksi; Sutaji Sutaji (Journal on Education, 2023)
The research aims to apply differentiation learning (Learning Styles), increase student activity, and increase learning outcomes in science content on the human respiratory system in the chapter on how the body processes air in fifth grade students at SDN Sukowati, Kapas District, Bojonegoro Regency. This research is a classroom action research involving two different learning styles, namely visual and kinesthetic. This study was divided into two cycles (cycles I and II) beginning with the stages of planning, implementing, observing, evaluating and reflecting. The research was conducted in class V at Sukowati Elementary School, Kapas District, Bojonegoro Regency for the 2022/2023 academic year. The results of the research carried out by 25 students. In the first cycle, the application of teacher activity differentiation learning had a percentage of 69%, while the first cycle of student activity reached 88%, an increase from the pre-action activities. In cycle II teacher activity increased to 94% and student activity to 100%. Another result, an increase in learning outcomes also occurs in differentiation learning research. In the first cycle, the classical average value was 72 with the percentage of students completing 56%. This means that with the KKM that must be achieved, namely 76, there are 14 students who have completed and 11 students who have not completed. In cycle II student learning outcomes also increased. This was proven in cycle I to get an average classical value of 85 with a success percentage of 100%. This means that with the KKM achieved, namely 76, there are 24 students who complete and 1 student who has not completed. This means that with the KKM achieved, namely 76, there are 25 students who have completed and no students who have not completed.